HYPNOTEACHING AS AN ALTERNATIVE APPROACH IN ARABIC LANGUAGE LEARNING - Mochamad Gilang Ardela Mubarok; Sugih Ardianto; Izzuddin Mustafa; Hana Hazim Nashif Kanz (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2026)
This study aims to examine the potential of hypnoteaching as an alternative approach to overcoming psychological barriers in Arabic language learning. Arabic classes in Indonesia are often hindered by learners’ low interest, fear of making mistakes, and lack of confidence, while existing approaches tend to focus on grammatical, communicative, or technology-based methods without sufficiently addressing learners’ mental-emotional dimensions. Using a qualitative method with a library research design, this study analyzes books, journal articles, and research reports that explicitly discuss hypnoteaching and Arabic language learning from educational and psychological perspectives. The data were analyzed through descriptive–analytical reading, thematic coding, and critical comparison of theoretical and empirical findings related to suggestion, motivation, and anxiety reduction in learning. The results show that hypnoteaching, when implemented through structured positive suggestion, supportive classroom interaction, and simple relaxation stages, has strong potential to reduce fear and tension, increase interest and motivation, and support the development of skills such as speaking and vocabulary in Arabic. This study contributes to Arabic pedagogy by offering a cross-disciplinary conceptual framework that integrates hypnoteaching into Arabic learning as a more humanistic and student-oriented model, complementing conventional grammatical, communicative, and technology-based approaches.